2018
DOI: 10.1093/mnras/sty063
|View full text |Cite
|
Sign up to set email alerts
|

Abell 1367: a high fraction of late-type galaxies displaying H i morphological and kinematic perturbations

Abstract: To investigate the effects the cluster environment has on Late-Type Galaxies (LTGs) we studied HI perturbation signatures for all Abell 1367 LTGs with HI detections. We used new VLA H i observations combined with AGES single dish blind survey data. Our study indicates that the asymmetry between the high-and low-velocity wings of the characteristic double-horn integrated H i spectrum as measured by the asymmetry parameter, A flux , can be a useful diagnostic for ongoing and/or recent HI stripping. 26% of A1367 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 65 publications
4
63
1
Order By: Relevance
“…• We find no correlations between H i asymmetries and either stellar or H i mass. The lack of correlation with H i mass is in disagreement with the results of Scott et al (2018) for Virgo cluster galaxies. Scott et al (2018) found a larger asymmetric fraction (42%) of galaxies with H i masses log(M HI /M ) ≤ 8.48 compared with 16% with log(M HI /M ) > 8.48 (117 and 90 galaxies, respectively) and is potentially due to the small sample size used in this work (136 galaxies).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…• We find no correlations between H i asymmetries and either stellar or H i mass. The lack of correlation with H i mass is in disagreement with the results of Scott et al (2018) for Virgo cluster galaxies. Scott et al (2018) found a larger asymmetric fraction (42%) of galaxies with H i masses log(M HI /M ) ≤ 8.48 compared with 16% with log(M HI /M ) > 8.48 (117 and 90 galaxies, respectively) and is potentially due to the small sample size used in this work (136 galaxies).…”
Section: Discussioncontrasting
confidence: 83%
“…Probing morphological and kinematic asymmetries requires observations with similar physical scales, as decreasing resolution can smooth out flux and velocities or produce offsets in the H i defined centre of the galaxy (e.g. Scott et al 2018). Nearby galaxies with higher physical scale resolution can be smoothed to match the lower resolutions of more distant galaxies, which will increase the sample size for direct comparison of morphological and kinematic asymmetries and enable the comparison of galaxies at a greater range of distances.…”
Section: Implications For Wallabymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are already published values for the integrated flux and velocity width of each spectrum in the xGASS catalogue we have made our own measurements of these parameters using our fits as they provide a less subjective measure of the limits of each spectrum and allow us to measure velocity widths at the 20% level, compared to the published xGASS values measured at the 50% level (ω 50 ), to be consistent with previous global Hi asymmetry studies (e.g. Espada et al 2011;Scott et al 2018;Bok et al 2019). We measure a median relative difference of -4.2% and -4.3% in integrated flux and velocity width compared to the existing xGASS measurements, but this can be attributed to differences in the measurement techniques and identification of spectrum peaks.…”
Section: Spectra Fittingsupporting
confidence: 74%
“…The value of an A flux deviating by 1 σ from the mean of that distribution is then 1.13. A study by Scott et al (2018) indicated that A flux is quite sensitive to recent ( 0.7 Gyr) interactions which impact H i disks. For UGC 2162 A flux = 1.07 ± 0.13, measured from the GBT H i spectrum, which is within the 1 σ value from the isolated sample.…”
Section: H I Kinematicsmentioning
confidence: 99%